Psychological Morbidity and Quality of Life in Women with Abnormal Uterine Bleeding - Khan, Muhammad Muslim; Fatima, Fatima; Naila, Naila; Jamal, Izaz; Gul, Ijaz; Muneeb, Pirzada (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abnormal uterine bleeding (AUB) is a common gynaecological condition that adversely affects women’s physical health, emotional stability, and social functioning. Chronic or excessive menstrual bleeding can result in anaemia, fatigue, and reduced daily productivity. These persistent symptoms often predispose affected women to psychological morbidity, particularly depression and anxiety, which further compromise overall health-related quality of life. Objectives: To determine the frequency of depression and anxiety among women with abnormal uterine bleeding and to evaluate the association between psychological morbidity and impairment in quality of life. Methodology: This cross-sectional study was conducted in the gynaecology department of a tertiary care hospital. A total of 100 women aged 18–50 years diagnosed with abnormal uterine bleeding were enrolled using non-probability consecutive sampling. Women with pre-existing psychiatric disorders or chronic systemic illnesses were excluded. Depression and anxiety were assessed using validated screening scales, while quality of life was evaluated using a standardised health-related quality-of-life questionnaire. Sociodemographic and clinical characteristics were recorded. Statistical analysis was performed using SPSS version 24.0, applying chi-square and independent t-tests, with a p-value < 0.05 considered statistically significant. Results: The mean age of participants was 38.6 ± 7.9 years. Depression was observed in 46% of women, while 39% exhibited clinically significant anxiety. Depression was significantly associated with longer bleeding duration and lower hemoglobin levels (p = 0.002). Anxiety was more prevalent among women with heavy menstrual bleeding and cycle irregularity (p = 0.01). Quality-of-life scores were significantly lower in women with depression compared to those without (42.3 ± 9.6 vs. 58.7 ± 10.4; p < 0.001). Anxiety was also significantly associated with poor quality-of-life outcomes (p = 0.003). Conclusion: Psychological morbidity is highly prevalent among women with abnormal uterine bleeding and is strongly associated with reduced quality of life. Incorporating routine psychological screening and multidisciplinary care into AUB management may improve overall patient outcomes.